Small Bowel Obstruction by Broad Ligament Hernia: Three Case Reports, Management and Outcomes - Fernandes, Manuela Graça; Loureiro, Ana Rita Mateus; Obrist, Maria João Diogo; Prudente, César (Acta Médica Portuguesa, 2019)
Internal hernias are a rare cause of bowel obstruction (1%) and can be caused by broad ligament defects in 4% to 7% of the cases. These defects may be congenital or acquired and are classified according to its anatomical location. This paper reports three cases of small bowel obstruction by broad ligament hernia. The patients, three women aged from 35 to 51 years old, were admitted to the emergency department with small bowel obstruction. An exploratory laparotomy was performed during which an internal hernia through a broad ligament defect was identified. In all cases the hernia content was reduced and the defect closed. One of the patients required a segmental enterectomy. All patients had a favorable outcome. This paper aims to raise awareness about the broad ligament hernia as a cause of bowel obstruction, namely in middle-aged women with no surgical history.